The Concept and the Reality of Evaluating Teachers by Students - Banaszyk, Piotr (Studia Oeconomica Posnaniensia, 2017)
The article is devoted to the issue of the evaluation of academic teachers carried out by students. Legal obligations to carry out all the higher education institutions creates the risk of giving control operations which are only formal in nature. Included were: eclectic status assessment, the lack of representativeness of surveys and questionnaires’ inadequacy of assessments in relation to the specificity of teaching.